Convergent approach to persistent atrial fibrillation ablation: long-term single-centre safety and efficacy - Carpenter, Alexander; Pannell, Laura M. K.; Rizvi, Syed I. A.; Maciver, Kirsty; Rajakaruna, Cha; Ciulli, Franco; Duncan, Edward R.; Thomas, Glyn; Barman, Palash; Bond, Richard; Nisbet, Ashley M. (Frontiers in Cardiovascular Medicine, 2024)
Background Efforts to maintain sinus rhythm in patients with persistent atrial fibrillation (PsAF) remain challenging, with suboptimal long-term outcomes. Methods All patients undergoing convergent PsAF ablation at our centre were retrospectively analysed. The Atricure Epi-Sense® system was used to perform surgical radiofrequency ablation of the LA posterior wall followed by endocardial ablation. Results A total of 24 patients underwent convergent PsAF ablation, and 21 (84%) of them were male with a median age of 63. Twelve (50%) patients were obese. In total, 71% of patients had a severely dilated left atrium, and the majority (63%) had preserved left ventricular function. All were longstanding persistent. Eighteen (75%) patients had an AF duration of >2 years. There were no endocardial procedure complications. At 36 months, all patients were alive with no new stroke/transient ischaemic attack (TIA). Freedom from documented AF at 3, 6, 12, 18, 24, and 36 months was 83%, 78%, 74%, 74%, 74%, and 61%, respectively. There were no major surgical complications, with five minor complications recorded comprising minor wound infection, pericarditic pain, and hernia. Conclusions Our data suggest that convergent AF ablation is effective with excellent immediate and long-term safety outcomes in a real-world cohort of patients with a significant duration of AF and evidence of established atrial remodelling. Convergent AF ablation appears to offer a safe and effective option for those who are unlikely to benefit from existing therapeutic strategies for maintaining sinus rhythm, and further evaluation of this exciting technique is warranted. Our cohort is unique within the published literature both in terms of length of follow-up and very low rate of adverse events.